2019
DOI: 10.1111/are.14221
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional characterization of glutamine synthetase from giant freshwater prawn (Macrobrachium rosenbergii) under osmotic stress

Abstract: The freshwater prawn, Macrobrachium rosenbergii naturally lives in the freshwater, though it migrates to the brackish water environment during spawning that claimed to be resistant on a broad range of saline fluxes. However, little is known about the osmoregulatory patterns and the effect of an enzyme glutamine synthetase (GS) in M. rosenbergii under stress. Here, we described the identification and functional characterization of GS from M. rosenbergii (Mr-GS) at molecular and protein levels. The identified Mr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A previous report found that the GS gene has osmo-regulation properties in the osmotic stress environments. Moreover, GS participated in osmo-regulating the toxic ammonia and increased the Gln levels in the tissues [44]. Furthermore, the mRNA expression was significantly upregulated in the P. cristata during the osmotic challenge in the encystment.…”
Section: Discussionmentioning
confidence: 95%
“…A previous report found that the GS gene has osmo-regulation properties in the osmotic stress environments. Moreover, GS participated in osmo-regulating the toxic ammonia and increased the Gln levels in the tissues [44]. Furthermore, the mRNA expression was significantly upregulated in the P. cristata during the osmotic challenge in the encystment.…”
Section: Discussionmentioning
confidence: 95%
“…The RNA was isolated and RNase-free DNase I (Sangon, Shanghai, China) treatment was administered to remove any possible contamination by genomic DNA. Using a biophotometer (Eppendorf, Hamburg, Germany), the concentration of the total RNA in each sample was noted, after which 1% agarose gel was used per 2 μL for electrophoresis to evaluate all the sample’s integrity [ 42 ]. Each RNA had their first-strand cDNA developed to make real-time reverse transcription-quantitative polymerase chain reaction (qRT-PCR) possible; this was done with 1 μL of the total RNA, 4 μL of 5× iScript reaction mix (Bio-Rad, Hercules, CA, USA), and 1 μL iScript reverse transcriptase in a final volume of 20 μL.…”
Section: Methodsmentioning
confidence: 99%
“…The membranes were then rinsed for 5 min in three repetitions with TBST and also incubated with HRP-conjugated secondary antibody goat anti-rabbit IgG (1/10,000 dilution) for 55 min. Another three repeats for 5 min washing with TBST were done [ 42 ]. This led to the revealing and measurement of the immunoreactive bands by chemiluminescence (ECL Western Blotting Substrate, Solarbio, Beijing, China) and ChemiScope 6000 (CliNX, Shanghai, China), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole formation was depicted as a mean ± SD (standard deviation) at least 3 separate tests. The statistical importance of the information was evaluated by ANOVA (one-way analysis of variance), and GraphPad Prism 7 was used to draw gures [31]. The difference was considered important when P < 0.05 (*).…”
Section: Statistical Evaluationmentioning
confidence: 99%